Pengaruh Perlakuan Ekstraksi Limbah Ampas Kopi terhadap Sifat Mekanis Komposit Bermatriks Polipropilena - Melyna, Ella; Syiar, Raizy Ziman (Rekayasa Material, Manufaktur dan Energi, 2023)
The rapid development of technology and science produces renewable versatile ideas and products. This study examines the use of coffee grounds as filler for polymer composites. The polymer used is a polypropylene thermoplastic polymer. The use of spent coffee grounds can reduce environmental waste. The oil content in coffee grounds is hydrophobic, while the polypropylene matrix itself is hydrophilic. The purpose of extracting coffee grounds is to remove the oil content in coffee grounds, with reduced oil and water content, the adhesion between the polypropylene surface and the coffee grounds will be better. The manufacture of polymer composites uses a Manual Forming Machine (MFM) with a variety of additions of extracted coffee grounds to polypropylene. The results of the study stated that the extraction treatment on coffee grounds increased the values of tensile strength, impact strength, and flow rate compared to the addition of coffee grounds without extraction, but variations in the addition of coffee grounds decreased the values of tensile strength, impact strength and flow rate. The highest variation in the polypropylene matrix composite with the addition of 5% coffee grounds waste extraction resulted in a tensile strength of 20.22 MPa, an impact strength of 2.398 kJ/m², and a flow rate value of 8.48 g/10 minutes. The extraction process removes the oil content. This is evidenced by the loss of ester groups in the functional group test results of the extracted coffee grounds waste.